Perception About Pain Relief During Normal Labour Among Health Care Providers Conducting Delivery - Tasnim, Saria (Medicine Today, 2012)
Medicine Today 2009 Volume 21 Number 02 Page 64-67 DOI: http://dx.doi.org/10.3329/medtoday.v21i2.12548